Update zur Diagnose und Therapie der Sarkopenie - Goisser, Sabine; Bauer, Jürgen M. (Der Internist, 2019)
Since 2016 sarcopenia, the age-associated loss of muscle mass, strength and function, has the ICD-10-GM code M62.50 (International Statistical Classification of Diseases and Related Health Problems, 10th Revision, German Modification). The diagnosis of sarcopenia requires the combined presence of low muscle strength and low muscle mass. Well-established approaches for the prevention and therapy of sarcopenia are exercise programs—in particular strength, endurance and power training—and nutritional interventions, preferably a combination of both. Adequate protein intake is considered highly relevant, while the role of other nutrients involved in muscle metabolism (e. g. creatine, vitamin D, antioxidants, omega-3 fatty acids) is less clear, being still the subject of controversial discussions. Innovative pharmacological therapies are currently under investigation and their future relevance for this indication is unclear. In general, it has to be stated that there are still only few intervention studies available that focused specifically on sarcopenia in older individuals. More studies in this rapidly increasing population are urgently needed.